Disinfector‐Assisted Low Temperature Reduced Graphene Oxide‐Protein Surgical Dressing for the Postoperative Photothermal Treatment of Melanoma. (8th July 2022) - Wu, Yuanhao; Yang, Junyao; van Teijlingen, Alexander; Berardo, Alice; Corridori, Ilaria; Feng, Jingyu; Xu, Jing; Titirici, Maria‐Magdalena; Rodriguez‐Cabello, Jose Carlos; Pugno, Nicola M; Sun, Jiaming; Wang, Wen; et al.
Abstract: Materials that combine the functionalities of both of proteins and graphene are of great interest for the engineering of biosensing, drug delivery, and regenerative devices. Graphene oxide (GO) offers an opportunity to design GO‐protein interactions but the need for harsh reduction processes to enable GO photoexcitation remains a limitation. A disinfector‐assisted low temperature method to reduce GO‐protein materials and fabricate surgical dressings with tuneable photothermal efficiency and bioactive properties for the postoperative treatment of melanoma is reported. The approach harnesses the capacity of 70% ethanol to penetrate the protein shell of microorganisms to infiltrate GO‐protein complexes and reduce GO at low temperature (85 °C) while maintaining the material structure and bioactivity. Both experiments and coarse‐grained simulations are used to describe the reduction process and assess the material properties. In vitro and in vivo validation revealed the capacity of the dressings to prevent tumor recurrence and promote healing after tumor resection. Abstract : A method harnessing the capacity of 70% ethanol to penetrate the protein shell of microorganisms is reported to reduce GO‐protein complexes at low temperature (85 °C) and enable the fabrication of bioactive and conductive surgical dressings. The dressings are used for the postoperative treatment of melanoma and shown to prevent tumor recurrence and promote wound healing in a mice model.